2022
DOI: 10.3390/agronomy12102461
|View full text |Cite
|
Sign up to set email alerts
|

PotatoMASH—A Low Cost, Genome-Scanning Marker System for Use in Potato Genomics and Genetics Applications

Abstract: We have developed PotatoMASH (Potato Multi-Allele Scanning Haplotags), a novel low-cost, genome-scanning marker platform. We designed a panel of 339 multi-allelic regions placed at 1 Mb intervals throughout the euchromatic portion of the genome. These regions were assayed using a multiplex amplicon sequencing approach, which allows for genotyping hundreds of plants at a cost of 5 EUR/sample. We applied PotatoMASH to a population of over 700 potato lines. We obtained tetraploid dosage calls for 2012 short multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…With the low cost of next-generation sequencing, genotyping-by-sequencing (GBS) strategies are an interesting option. GBS strategies can include a step of genome complexity reduction using restriction enzymes (Elshire et al, 2011), capture baits (Uitdewilligen et al, 2013), or amplicon sequencing like potatoMASH (Leyva-Pérez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…With the low cost of next-generation sequencing, genotyping-by-sequencing (GBS) strategies are an interesting option. GBS strategies can include a step of genome complexity reduction using restriction enzymes (Elshire et al, 2011), capture baits (Uitdewilligen et al, 2013), or amplicon sequencing like potatoMASH (Leyva-Pérez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although the pattern (Fig. 3 ) and proportion (data not shown) of GBS SNPs in euchromatic and heterochromatic regions, as described by Sharma et al ( 2013 ) and Leyva-Perez et al ( 2022 ), for chromosome 8 did not significantly differ from rest of the chromosomes, the pronounced shift in LD decay rate for this chromosome using GBS SNPs is somewhat intriguing.…”
Section: Discussionmentioning
confidence: 47%
“…Numerous studies have successfully reported application of GWAS in potato (Berdugo-Cely et al 2017 ; Carley et al 2017 ; D’hoop et al 2008 , 2014 ; Fischer et al 2013 ; Kloosterman et al 2013 ; Lindqvist-Kreuze et al 2014 ; Rosyara et al 2016 ; Schönhals et al 2016 ; Sharma et al 2018 ; van Eck et al 2017 ; Vos et al 2017 ). Reports involving other SBG approaches in potato, especially for low cost genome scanning, are also emerging (Leyva-Perez et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…We generated marker data for all three populations using the amplicon sequencing strategy potatoMASH (Leyva-Pérez et al 2022 ). DNA extraction, library preparation, and bioinformatic processing of sequencing reads to obtain marker dosages were performed according to Leyva-Pérez et al ( 2022 ), with the exception that we aligned short-reads to DM v6.1 (Pham et al 2020 ) instead of DM v4.03. Unique amplicon alleles, referred to as haplotags, were used as genetic markers.…”
Section: Methodsmentioning
confidence: 99%